Changes in social distance among Croatian high school students as an indicator for further education reforms - Blažević Simić, Ana (Array, 2013)
During the last decade, the Croatian educational system has undergone many changes and huge reforms. Some of their key priorities - intercultural education, a European dimension to education, social and civic competence, cultural awareness and expression and also the education of national minorities - have been recognized. However, since the early years of Croatian independence, 1993 and 1998, no further research on social distance attitudes of Croatian students towards ethnic and religious groups has been done. Therefore, in 2009, data was gathered from 27 Croatian high schools using the Bogardus Social Distance Scale to examine social distance towards ethnic and religious groups and to determine whether it has been reduced in comparison with the data from the previous studies. The first published results (by the same author) of a simple analysis of variance with the additional Scheffe’s test showed that, out of all the respondents, the male students, the students in lower grade classes, mostly the students from the region of Osijek, those of Croatian ethnicity and Catholic religion, are likely to have a negative opinion. In addition, this paper examines social distance in relation to three additional independent variables: type of school, student grades and education of parents. Based on the same statistical analysis, the author presents that, of all respondents, in the crafts and artistry schools, those with unsatisfactory or satisfactory school work performance and those whose parents have a lower degree of education are particularly more likely to have a negative opinion.